The evolution of sentencing policy and practice in England and Wales, 2003–2015 - Roberts, J; Ashworth, A (University of Chicago Press, 2016)
Sentencing in England and Wales evolved in a direction from other common law countries. Although sentencing problems found in many Western nations are present, legislative and judicial responses have been very different. Use of custody rose steeply in the 1990s and has remained stable around that level in recent years. Crimes of violence and sexual aggression have, however, attracted increasingly longer sentences. The other principal changes are a steep increase in indeterminate sentences, now accounting for some 19 percent of the prison population, and a striking rise in the use of suspended sentences that has reduced the use of community sentences rather than terms of imprisonment. Net widening has occurred. The principal distinction between England and most other jurisdictions is that statutorily binding guidelines now exist for both magistrates' and higher courts. Unlike most US guidelines that assign offenses to levels of seriousness within a single sentencing grid, the English guidelines are offense specific. THe Sentencing Council has also issued "generic" guidelines applying to all categories of offending. The guidelines have been evolving for over a decade. Growing but still limited research suggests modest positive effects.